Single and combined association between brominated flame retardants and cardiovascular disease: a large-scale cross-sectional study - Yin, Wenhao; Xu, Rui; Zou, Jiyu; Wang, Yaqin; Zhang, Yan (Frontiers in Public Health, 2024)
The single and combined association between brominated flame retardants (BFRs) and cardiovascular diseases (CVD) has remained unelucidated. This research aimed at exploring the associations between mixture of BFRs and CVD. This research encompassed adult participants from the National Health and Nutrition Examination Survey in 2005-2016. The weighted quantile sum (WQS) model and quantile g-computation (QGC) model were applied to examine the combined effects of BFRs mixture on CVD. In this research, overall 7,032 individuals were included. In comparison with the lowest quartile, the highest quartile of PBB153 showed a positive association with CVD, with odds ratio (OR) values and 95% confidence intervals (CI) of 19.2 (10.9, 34.0). Furthermore, the acquired data indicated